Efektivitas Program Cabri 3D dalam Meningkatkan Hasil Belajar Matematika Siswa - Nurfazriyah, Sri Mulyani; Sudianto, Sudianto (Polinomial : Jurnal Pendidikan Matematika, 2025)
Learning mathematics in the field of spatial geometry still presents challenges in the form of poor student outcomes. This is due to difficulties in understanding abstract concepts. Using technology-based learning media is seen as one solution to this problem. This study aims to analyse this problem and find ways to overcome it. This study aims to analyse the effectiveness of using Cabri 3D to improve mathematics learning outcomes. A Systematic Literature Review was conducted to examine this. This involved examining Sinta-accredited articles published between 2019 and 2025. Data were obtained through literature searches and analysed using Qualitative descriptive analysis techniques. The results of the study indicate that using Cabri 3D consistently improves learning outcomes, conceptual understanding and mathematical spatial abilities, especially in subjects that require high levels of visualisation. This study concludes that Cabri 3D is an effective and relevant learning medium. to improve the quality of mathematics education in schools.